2021
DOI: 10.1101/2021.11.28.470279
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Processing of oxidatively damaged DNA dirty ends by APE1

Abstract: Reactive oxygen species attack the structure of DNA, thus altering its base-pairing properties. Consequently, oxidative stress-associated DNA lesions are a major source of the mutation load that gives rise to cancer and other diseases. Base excision repair (BER) is the pathway primarily tasked with repairing DNA base damage, with apurinic/apyrimidinic endonuclease (APE1) having both AP-endonuclease and 3’ to 5’ exonuclease (exo) DNA cleavage functions. The lesion 8-oxo-7,8-dihydroguanine (8-oxoG) can enter the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(114 reference statements)
0
1
0
Order By: Relevance
“…Mutation of R177 to alanine results in only subtle increases in kinetic rate for both the AP-endonuclease and proofreading exonuclease activities 31, 39 . However, a recent publication reported that R177A decreased APE1 activity when processing a 3’-8oxoG lesion, indicating R177 plays an important role in mechanism of 8oxoG processing by APE1 53 .…”
Section: Discussionmentioning
confidence: 94%
“…Mutation of R177 to alanine results in only subtle increases in kinetic rate for both the AP-endonuclease and proofreading exonuclease activities 31, 39 . However, a recent publication reported that R177A decreased APE1 activity when processing a 3’-8oxoG lesion, indicating R177 plays an important role in mechanism of 8oxoG processing by APE1 53 .…”
Section: Discussionmentioning
confidence: 94%